Effect Entrepreneur Innovation In Shopping Habit Customer In Marketplace Tokopedia - Hartono Subagio (Publikasi Indonesia, 2023)
The development of technology and e-commerce has brought significant changes in consumer shopping behaviour. Online marketplaces such as Tokopedia have become one of the popular platforms for consumers to shop online. The main objective of this study is to identify and analyse the effect of entrepreneurial innovation on customer shopping habits on Tokopedia. This study uses a quantitative research method with a survey research design. Data is collected through distributing questionnaires to Tokopedia customers. The data collected through the questionnaire will be analysed using regression analysis techniques. The results showed that entrepreneur innovation affects customer shopping habits at the Tokopedia Marketplace. Entrepreneurial innovation creates more exciting and varied products or services. Tokopedia, as an e-commerce platform, is a forum for various entrepreneurs to present new and unique products. The availability of these diverse products encourages customer interest to continue exploring and shopping on Tokopedia